MASTITE BOVINA: RELATO DE CASO - Lenhart, Daniel de Souza; Paulino, Greiciane Alves; Parise, Sabrina; Alves, Bruna Farias; Daneluz, Marina de Oliveira; Ansilieiro, Willian Jonas (Anais de Medicina Veterinária, 2022)
.